Development of medical termination of pregnancy: a review. (27th September 2017) - Ho, PC
Abstract : The synthesis of mifepristone, an antiprogestin blocking the action of progesterone at the receptor level, started a new era of medical termination of pregnancy (MTOP). The initial results of MTOP with mifepristone alone were disappointing; however, mifepristone can sensitise the myometrium to the action of prostaglandins. Clinical trials have shown that the sequential administration of mifepristone followed 1–2 days later by a prostaglandin analogue is a safe, effective, and acceptable method for MTOP. This article will review the events and challenges leading to the development of the current evidence‐based and yet off‐label regimen for first‐trimester MTOP. Tweetable abstract: This article reviews the events and challenges in the development of medical termination of pregnancy. Tweetable abstract: This article reviews the events and challenges in the development of medical termination of pregnancy.